2013
DOI: 10.1107/s010827011302859x
|View full text |Cite
|
Sign up to set email alerts
|

Methanesulfonic acid salt forms of carbamazepine and 10,11-dihydrocarbamazepine

Abstract: New methanesulfonic acid salt forms of the anticonvulsant and analgesic active pharmaceutical ingredient carbamazepine and its closely related structural analogue 10,11-dihydrocarbamazepine have been prepared and characterized by single-crystal X-ray diffraction at 120 and 100 K, respectively {namely [(5H-dibenzo[b,f]azepin-5-yl)(hydroxy)methylidene]azanium methanesulfonate, C15H13N2O(+)·CH3SO3(-), and [(10,11-dihydro-5H-dibenzo[b,f]azepin-5-yl)(hydroxy)methylidene]azanium methanesulfonate, C15H15N2O(+)·CH3SO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 23 publications
(26 reference statements)
3
21
0
Order By: Relevance
“…2 is therefore a salt at this temperature 46 whilst the refined H-atom positions at 100 K for 3 indicate a centralised position (the d O-H 1.23(7) Å and d H⋯O 1.26(7) Å distances are not significantly different given the esds) meaning it is an intermediate between a salt and co-crystal. 47 Generally, where the interaction has a charge assisted component (O + -H⋯O − ), as in 2 and 3, the donor-acceptor distances are shorter. This can be explained where the charges on the donor-acceptor atoms significantly increase the strength of the interaction 33 by reinforcing its electrostatic character; 48,49 leading to the shorter donor-acceptor distances.…”
Section: Resultsmentioning
confidence: 99%
“…2 is therefore a salt at this temperature 46 whilst the refined H-atom positions at 100 K for 3 indicate a centralised position (the d O-H 1.23(7) Å and d H⋯O 1.26(7) Å distances are not significantly different given the esds) meaning it is an intermediate between a salt and co-crystal. 47 Generally, where the interaction has a charge assisted component (O + -H⋯O − ), as in 2 and 3, the donor-acceptor distances are shorter. This can be explained where the charges on the donor-acceptor atoms significantly increase the strength of the interaction 33 by reinforcing its electrostatic character; 48,49 leading to the shorter donor-acceptor distances.…”
Section: Resultsmentioning
confidence: 99%
“…Since no complexes exhibit negative ΔpKa values, pure cocrystal formation is almost unlikely and has not been observed. [26].…”
Section: Resultsmentioning
confidence: 99%
“…[1,7] This effect was so diagnostic of neutral and cationic species that it could even be used to assign "intermediate" status to structures where the acidic proton was in dynamic equilibrium between CBZ(H) and an O atom of a second crystal component. [6,8] A similar analysis of bond length variation for the known PAR(H) species (Scheme 2) is shown in Figure 3. As with CBZ and DCBZ, it is clear that protonated and neutral PAR species show different geometries with the C=O bond lengthening by approximately 0.05 to 0.06 Å and C-N shortening by 0.03 to 0.04 Å upon protonation.…”
Section: Resultsmentioning
confidence: 77%
“…[2] Since then several groups have crystallographically investigated series of multiple salt forms of particular amide APIs, notably the paracetamol work already mentioned above and structures of the model APIs carbamazepine (CBZ) and its congener dihydrocarbamazepine (DCBZ). [1,[6][7][8] The interest in looking at multiple related structures rather than single salt forms is of course the increased ability to compare and contrast both structures and the properties that arise from these structures. We are particularly interested in the CBZ and DCBZ studies that have shown systematic differences between the neutral and protonated forms in terms of both molecular structure and of typical hydrogen bonding motifs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation